Situation Report: Hungary, 17 April 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A Reorganization Puzzle: The Hungarian Gear and Elevator Enterprise Retail Trade Firms Introduce the Raffle Hungarian Sports Authority Reorganized Hungary Imports Wrecked Cars from West Germany Commission Work Promoted by Authorities International Poetry Conference in Budapest Increased Subsidies for Viniculture New Steps to Boost Corn Production